First case of bloodstream infection of Trichosporon loubieri in a patient with B-cell lymphocytic leukemia in China - Hu, Liqing; Wang, Shanshan; Sun, Dinghe; Chu, Jinguo; Lai, Binbin; Liu, Yanqing (Journal of infection and chemotherapy : official journal of the Japan Society of Chemotherapy, 2021)
Trichosporon loubieri is an opportunistic pathogenic fungus that could causes invasive infections for human, which rarely been reported. In the present study, we reported a case of bloodstream infection from a patient with Ph-positive B-cell acute lymphocytic leukemia (B-ALL) due to Trichosporon loubieri. Trichosporon loubieri was identified by Internal Transcribed Spacer (ITS) gene sequencing. The patient was treated by intravenous voriconazole (VCZ) and amphotericin B (AmB) according to antifungal susceptibility testing and he was still alive so far. To the best of our knowledge, this is the fourth report of human bloodstream infection due to Trichosporon loubieri and the first survival case of its kind in an immunocompromised patient.